2021
DOI: 10.1002/jcp.30285
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 inflammasome: Multiple activation pathways and its role in primary cells during ventricular remodeling

Abstract: Inflammasomes are a group of multiprotein signaling complexes located in the cytoplasm. Several inflammasomes have been identified, including NLRP1, NLRP2, NLRP3, AIM2, and NLRC4. Among them, NLRP3 was investigated in most detail, and it was reported that it can be activated by many different stimuli. Increased NLRP3 protein expression and inflammasome assembly lead to caspase‐1 mediated maturation and release of IL‐1β, which triggers inflammation and pyroptosis. The activation of the NLRP3 inflammasome has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 154 publications
0
17
0
Order By: Relevance
“…In addition to cardiovascular diseases such as ischemic heart disease, hypertension, and arrhythmia, inflammation also plays an important role in heart failure ( Pieske et al, 2019 ; Groenewegen et al, 2020 ; Schiattarella et al, 2020 ). Studies have shown that inflammatory factors can lead to ventricular remodeling, which in turn affects the development of heart failure ( Al-Taweel et al, 2017 ; Tan et al, 2021 ; Yan et al, 2021 ). In addition, there are also animal studies and clinical studies focusing on the positive effects of anti-inflammatory treatments on cardiovascular diseases ( Bäck and Hansson, 2015 ; Huang and Frangogiannis, 2018 ; Ma et al, 2019 ; Gao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cardiovascular diseases such as ischemic heart disease, hypertension, and arrhythmia, inflammation also plays an important role in heart failure ( Pieske et al, 2019 ; Groenewegen et al, 2020 ; Schiattarella et al, 2020 ). Studies have shown that inflammatory factors can lead to ventricular remodeling, which in turn affects the development of heart failure ( Al-Taweel et al, 2017 ; Tan et al, 2021 ; Yan et al, 2021 ). In addition, there are also animal studies and clinical studies focusing on the positive effects of anti-inflammatory treatments on cardiovascular diseases ( Bäck and Hansson, 2015 ; Huang and Frangogiannis, 2018 ; Ma et al, 2019 ; Gao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research indicates that activation of the NLRP3 inflammasome has a role in basic structural alterations in VR after AMI [ 40 ]. Cardiac pressure overload causes Ca 2+ influx and triggers the activation of NLRP3 inflammasome in cardiomyocytes, which results in the recruitment of cardiac macrophages, the formation of fibrosis, and the development of myocardial dysfunction [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…VR is an important factor leading to the poor prognosis of many cardiovascular diseases in the middle and late stages ( 39 ). Therefore, delaying VR is of great significance for improving the quality of life.…”
Section: Discussionmentioning
confidence: 99%